The Price of Unawareness: How the Ministry of Finance's Communication Crisis Exploded - Indrayani, Ratna (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
This article maps the Indonesian Ministry of Finance's communication crisis in 2023, which resulted from violence by the son of a ministry official. Using document search and issue tracking methods, the study found patterns of issue spread from the root of the crisis, triggering the crisis, hooking the crisis, neglecting the crisis, mishandling the crisis, and miscommunicating the crisis. Crisis mapping is essential to read the direction of the spread of issues and potential problems in the future so that appropriate communication can be handled to prevent the crisis from exploding and spreading uncontrollably.